Poemas e problemas : a poesia como elemento integrador entre língua materna e matemática - Silva, Shirlei Alexandra da (2022)
This dissertation presents the theoretical-methodological trajectory of the research developedin the Postgraduate Program in Teaching Natural Sciences and Mathematics (PPGECM), at UFMT – University Campus of Sinop. Its theme is the relationship between Mother Tongue,Poetry and Mathematics in the pedagogical practices of teaching Mathematics and MotherTongue. It is a qualitative-quantitative research, using the action research procedure. Themain objective of this study is: To investigate how poetry and problem solving can becomeintegrating elements in interdisciplinary practices of Mother Tongue and Mathematics. In thisway, we seek to answer the following questioning: How to unite Mother Tongue, Poetry,Mathematics and Problem Solving in an educational product that helps elementary schoolteachers in their pedagogical practices? We will discuss our research based on authors whoapproach themes related to ours. As a result of this study, we present the Educational Product(EP) created for elementary school teachers and students, which is composed of two elements:1- Interdisciplinary Literature Book “Poeminhas para conta” and 2- Teacher Support Material“Poeminhas para conta” to count: Problem Solving from the perspective of PortugueseLanguage and Mathematics”. In the present study, we seek to present the importance of theintertwining between Mathematics and Mother Tongue through an EP proposal that seeks tounite these two forms of languages in an interdisciplinary way, thus aiming to rescue themutual impregnation and complementarity of one with the other.